2020
DOI: 10.3389/fpsyg.2020.554678
|View full text |Cite|
|
Sign up to set email alerts
|

Together Apart: The Mitigating Role of Digital Communication Technologies on Negative Affect During the COVID-19 Outbreak in Italy

Abstract: The ongoing pandemic of COVID-19 has forced governments to impose a lockdown, and many people have suddenly found themselves having to reduce their social relations drastically. Given the exceptional nature of similar situations, only a few studies have investigated the negative psychological effects of forced social isolation and how they can be mitigated in a real context. In the present study, we investigated whether the amount of digital communication technology use for virtual meetings (i.e., voice and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(118 citation statements)
references
References 47 publications
5
110
0
3
Order By: Relevance
“…The same problems are reflected in the increase of digital media usage such as online-gaming or social media. Despite the fact, that the opportunity to digitally exchange with family and friends during the lockdown and thus to experience social support without social-physical presence or simply receive entertainment, proved to be a constructive coping strategy (6,11), studies have shown that addictive media usage increased during the lockdown (32). This is not surprising when digital communication and instrumental media usage for emotion regulation, remain one of the last possibilities to satisfy socio(physical) needs.…”
Section: Summary Of the Results And Implicationsmentioning
confidence: 99%
“…The same problems are reflected in the increase of digital media usage such as online-gaming or social media. Despite the fact, that the opportunity to digitally exchange with family and friends during the lockdown and thus to experience social support without social-physical presence or simply receive entertainment, proved to be a constructive coping strategy (6,11), studies have shown that addictive media usage increased during the lockdown (32). This is not surprising when digital communication and instrumental media usage for emotion regulation, remain one of the last possibilities to satisfy socio(physical) needs.…”
Section: Summary Of the Results And Implicationsmentioning
confidence: 99%
“…This development involved both the enhancement and standardization of already consolidated solutions in digital health and the exploration of new potentials such as those of the DCT [ 8 , 9 ]. In many cases, the simple mTech itself has represented a real lifebuoy [ 6 , 7 ] both for the continuation of normal activities (working and teaching) and for providing a safety net. However, this has not always happened in a uniform way.…”
Section: Discussionmentioning
confidence: 99%
“…The second role is to support teaching, work and relational activities in an exceptional way, allowing social distancing between subjects, such as through messaging and/or video conferencing and/or social network tools [ 6 , 7 ].…”
Section: The Covid-19: a Pandemic Exploded During The Mobile Technmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also useful for well-being interventions: those who are in quarantine or in nursing home can use technology to keep connected to their social ties. Indeed, a recent study has demonstrated that digital communications (i.e., voice and video calls, online board games and multiplayer video games, or watching movies in party mode) could maintain meaningful relationship and reduce negative psychological outcomes during the COVID-19 pandemic (Gabbiadini et al, 2020).…”
Section: Social Connectedness Mediated the Association Between Socialmentioning
confidence: 99%